Active management of third stage of labor: Assessment of standard of care in one of the training institute - Upadhyay, Meera; Sharma, Gaurav; Chataut, Dinesh (Nepal Journal of Obstetrics and Gynaecology, 2009)
Objective: To find out the quality of service (standard steps of the procedures) incorporated in the active management of the third stage of labor (AMTSL) in Maternity Hospital, Thapathali, Kathmandu, Nepal. Methods: Prospective (single blind) study, where the (uninformed) service providers had no knowledge that they were being assessed of their performances regarding the proper conduct of the AMTSL, in randomly selected 325 laboring women during all shifts of the day by 4 interns who carefully documented the findings in pre prepared standard 3 month duration reference during in the year 2061/2062 (2004/2005) in Maternity Hospital Thapathali, Kathmandu, Nepal. Results: (Pre) loading of oxytocin was correctly done immediately when the women were seen to bear down at second stage of labor. In 99.5% of cases (irrespective of duty shift). In 5.8 % of cases, the oxytocin doses were different from standard 10 units. The possibility of second twin was not ruled out in 81.9% before the administration of 10 units of IM oxytocin. Moreover, the study that controlled cord traction was revealed or showed applied in 50% of the cases without confirming uterine contraction while counter traction to the uterus was given in most of the cases (98.5%) along with effective examination of the placenta for its completeness in 98.2 % cases. Conclusion: This study shows that improvement in the standard AMTSL practices is still needed in the training providing institution, which demand ensuring the absence of twin tactfully before giving IM oxytocin within 2 minutes invariably after the delivery of the babies and also in giving slight traction on to the umbilical cord gently during uterine contraction along with counter traction to the uterus. Key words: Active management of third stage of labor AMTSL, oxytocin, uterine massage. doi:10.3126/njog.v1i2.2394 N. J. Obstet. Gynaecol Vol. 1, No. 2, p. 28-30 Nov-Dec 2006